2014
DOI: 10.1002/jbm.a.35078
|View full text |Cite
|
Sign up to set email alerts
|

PDLLA/PRGD/β‐TCP conduits build the neurotrophin‐rich microenvironment suppressing the oxidative stress and promoting the sciatic nerve regeneration

Abstract: A novel nerve guidance conduit comprising poly{(lactic acid)-co-[(glycolic acid)-alt-(l-lysine)]} (PRGD), poly (d,l-lactic acid) (PDLLA) and β-tricalcium phosphate (β-TCP) was constructed to facilitate the peripheral nerve regeneration. From the comparative study, PDLLA/PRGD/β-TCP conduit achieved the best recovery in regard of the ultrastructure observation and the SFI evaluation. At the first stage of the injury (7 days), the maximum expression augments in ZnSOD (6.4 folds) and GPX4 (6.8 folds) were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Interestingly, the regenerative effects achieved in the collagen/β‐TCP groups were superior to that in the collagen groups. This outcome came in a good agreement with others, in which the addition of β‐TCP added to the PRGD/PDLLA conduit‐enhanced sciatic nerve regeneration …”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the regenerative effects achieved in the collagen/β‐TCP groups were superior to that in the collagen groups. This outcome came in a good agreement with others, in which the addition of β‐TCP added to the PRGD/PDLLA conduit‐enhanced sciatic nerve regeneration …”
Section: Discussionsupporting
confidence: 90%
“…It was increased to more than 10 folds in the 100 µg/mL group, while it was increased to less than 6 folds in the group of 25 µg/mL. SWNTs-COOH treatments lead to more elevation in the GST expression in the 100 µg/mL after 24 h. [24] demonstrated the oxidative stress responses to carboxylic acid functionalized SWNTs on Similarly, Qiu et al [25] verified the rapid elevation of mRNA expressions of CAT, SOD, GPx after the nerve damaged to counteract oxidative stress. Therefore, the antioxidant system in neuron cells was greatly induced when cells were co-cultured with SWNTs in the present study.…”
Section: Resultsmentioning
confidence: 86%
“…Studies have shown that cell adhesion and growth was improved by adding a small amount of GRGDY. 11,12 of hydroxyapatite, interface bonding deteriorated and poor interfacial compatibility. The main reason is the lack of effective adhesion between HA and PDLLA interface.…”
Section: Amino Acid Content Of Testmentioning
confidence: 98%